1991
DOI: 10.1111/j.1365-2818.1991.tb03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron probe X‐ray microanalysis of intracellular element concentrations in cryosections in the presence of changes in cell volume

Abstract: SUMMARY The interpretation of element concentration data for X‐ray microanalyses of biological tissues, which are subjected to some experimental treatment, can be complicated by changes in cell volume and total cell dry matter induced by the treatment. We have examined the manner in which such changes would affect the values measured in frozen‐dried cryosections of soft tissues, and how they may be taken into account in the interpretation of the results. The element content (mass per unit dry weight) measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Quantification of the cellular elemental concentration in mmol/ kg wet weight was achieved by a comparison of the element characteristic X-ray signals obtained in the nuclei of cells with those of the albumin standard. The dry weight of the cells was determined by comparing the background radiation of the cellular spectra with that of the standard albumin layer as described by Bostrom et al (1991). The same authors also observed a high degree of correlation between cell volume and total cell dry matter.…”
Section: Preparation Of the Kidney For Electron Microprobe X-ray Analmentioning
confidence: 98%
“…Quantification of the cellular elemental concentration in mmol/ kg wet weight was achieved by a comparison of the element characteristic X-ray signals obtained in the nuclei of cells with those of the albumin standard. The dry weight of the cells was determined by comparing the background radiation of the cellular spectra with that of the standard albumin layer as described by Bostrom et al (1991). The same authors also observed a high degree of correlation between cell volume and total cell dry matter.…”
Section: Preparation Of the Kidney For Electron Microprobe X-ray Analmentioning
confidence: 98%